CRM Failure to Apply Optimal Management Information Systems: Case of Lebanese Financial Sector - Charbel Salloum; Jassem Ajaka (Arab Economic and Business Journal, 2013)
Financial markets in Lebanon are constrained by government influence, Islamic financial principles, and some barriers to foreign participation. Productivity in the Lebanese financial sector ranks below its occidental counterpart in spite the fact that regulatory, supervisory, and accounting standards are generally consistent with international norms. This paper aims to give the reasons and recommendations of the failure of applying the optimal management information system in the Lebanese Financial Sector. Our results show that the reasons include among others the systems by it selves, their functionalities, but also, companies' strategy and human capital issues.
Keywords: 330; Financial Sector; Banks; CRM and Capital Markets